Novel potential causative genes in carotid paragangliomas - Anastasiya V. Snezhkina; Elena N. Lukyanova; Andrew R. Zaretsky; Dmitry V. Kalinin; Anatoly V. Pokrovsky; Alexander L. Golovyuk; George S. Krasnov; Maria S. Fedorova; Elena A. Pudova; Sergey L. Kharitonov; Nataliya V. Melnikova; Boris Y. Alekseev; et al. (BMC, 2019)
Abstract Background Carotid paragangliomas (CPGLs) are rare neuroendocrine tumors that arise from the paraganglion at the bifurcation of the carotid artery and are responsible for approximately 65% of all head and neck paragangliomas. CPGLs can occur sporadically or along with different hereditary tumor syndromes. Approximately 30 genes are known to be associated with CPGLs. However, the genetic basis behind the development of these tumors is not fully elucidated, and the molecular mechanisms underlying CPGL pathogenesis remain unclear. Methods Whole exome and transcriptome high-throughput sequencing of CPGLs was performed on an Illumina platform. Exome libraries were prepared using a Nextera Rapid Capture Exome Kit (Illumina) and were sequenced under 75 bp paired-end model. For cDNA library preparation, a TruSeq Stranded Total RNA Library Prep Kit with Ribo-Zero Gold (Illumina) was used; transcriptome sequencing was carried out with 100 bp paired-end read length. Obtained data were analyzed using xseq which estimates the influence of mutations on gene expression profiles allowing to identify potential causative genes. Results We identified a total of 16 candidate genes (MYH15, CSP1, MYH3, PTGES3L, CSGALNACT2, NMD3, IFI44, GMCL1, LSP1, PPFIBP2, RBL2, MAGED1, CNIH3, STRA6, SLC6A13, and ATM) whose variants potentially influence their expression (cis-effect). The strongest cis-effect of loss-of-function variants was found in MYH15, CSP1, and MYH3, and several likely pathogenic variants in these genes associated with CPGLs were predicted. Conclusions Using the xseq probabilistic model, three novel potential causative genes, namely MYH15, CSP1, and MYH3, were identified in carotid paragangliomas.